Evaluation of anti-Helicobacter pylori antibodies level in sera of patients with chronic hepatitis B (World Journal of Experimental Biosciences, 2015)
The relationship between chronic hepatitis B virus and Helicobacter pylori infection was evaluated to determine, seventy five patients with chronic hepatitis B infection (8-70 years) were investigated. The results were compared with the results of 50 healthy volunteers. Anti-H. pylori antibodies IgA and IgG were measured by Indirect fluorescent antibody test (IFAT) in sera of patients and healthy groups. The percentage of anti-H.pylori IgA antibodies (26.67%) were significantly (P<0.01) higher than healthy control group. While, no significant difference was found between the percentages of anti-H. pylori IgG antibodies (48 %) in patient sera and these kind of antibodies in sera of healthy control group (P > 0.05). The present results indicated that the acute infection with H. pylori may be correlated with severity of chronic hepatitis B infection.